Qui sont nos ennemis? Qui sont nos amis? La presse pakistanaise et ses perceptions des attitudes et politiques de quatre grandes puissance 1958-1965. - Hassan, Ashraful; Burton, Bruce; Soderlund, W.C. (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
Utilizing content analysis methodology, this paper studies Pakistani press perceptions of external sources of threat and support covering the Period 1958-1965.From the literature on Pakistani foreign policy, seven specific hypotheses are extractedfor testing:1 - during the period 1958-1965, India was perceived to be the major threat toPakistan ;2 - the perception of India as the major threat increased sharply from 1962 onwards;3 - in 1959 China was perceived to be a greater threat to Pakistan than India was;4 - the Soviet Union was perceived to be the major threat in 1958, a significant butsecondary threat in 1959, the main threat again in 1960, and an insignificantthreat from 1961 onwards;5 - at no time during the period 1958-1965 was the United States perceived to be athreat to Pakistan;6 - the respective policies of China, the US.S.R., and the U.S. towards South Asia ingeneral and on the Kashmir issue in particular, played a major part in determiningPakistan's attitudes toward these states;7 - U.S. arms aid to India in 1962 resulted in a major Pakistani disillusionment withthe United States and this was accompanied by more positive Pakistani viewstoward the US.S.R. and China.Our data drawn from front page news stores and editorials appearing in a sample of the Pakistani newspaper Dawn, confirm in general terms hypotheses 1, 2, 5, 6, and 7, but fall to confirm hypotheses 3 and 4.Overall, the data point to the significance of the Sino-Indian border war in the fall of 1962 as a crucial turning point in Pakistan 's foreign policy alignments. Specifically, we see evidence of a turning away from the United States, combined with a movement toward China. Attitudes toward the Soviet Union were ambivalent.